Structural, dynamical, and thermodynamical properties of carbon nanotube polycarbonate composites: a molecular dynamics study - Chakraborty, Souvik; Roy, Sudip (Journal of Physical Chemistry B, 2012)
All-atom molecular dynamics simulations are performed on pure monomer and trimer of polycarbonate and their mixtures with different molecular weight percentages of embedded single walled carbon nanotubes at different temperatures to study the structural and dynamical properties of the composite system. The diffusion behaviors of monomer, trimer of polycarbonate and carbon nanotubes in composite matrices are investigated and compared with pure matrices in details. Both structural and dynamical properties indicate the weak interaction between the nanotubes and matrix molecules. The high tendency of nanotubes to form bundles is observed during simulation. The bundle formation free energy has been calculated from the potential of mean force calculations. The mechanism and energetics of bundle formation is explored in the atomistic scale. The formation of the carbon nanotube bundle is a favorable process in the oligomeric polycarbonate matrix.